Sistem Informasi Manajemen Personel Satbrimob Polda Kalbar - Suhardi Suhardi; Novi Safriadi; Haried Novriando (Jurnal Aplikasi dan Riset Informatika, 2023)
Administrative Affairs or abbreviated as Urmin in the West Kalimantan Police Mobile Brigade Unit Sub-division is a unit of function in charge of serving personnel administration, namely promotions and periodic salary increases, in proposing administrative files and personnel data, presentation of personnel data in the Brimob Unit or abbreviated as Satbrimob The West Kalimantan Regional Police are currently still using mutation books and Microsoft Office which are not systematically arranged, resulting in difficulties in finding and recording personnel data as a result in 2019 as many as 110 personnel were not submitted for issuance of periodic salary increases and 3 personnel were not proposed for promotions. According to the personnel strength report in March 2021, currently the number of Satbrimob Polda West Kalimantan personnel is 902 personnel, with the acceptance of Polri members every year, the number of members will always increase. Based on this background, the author wants to design and create an information system that can not only store personnel data, but can manage personnel data as needed by Urmin Subbagrenmin Satbrimob Polda West Kalimantan staff. The application is tested using a Black Box and UAT (User Acceptance Testing). Based on the results of the black box test, it shows that the system created has worked well and the system built according to the needs and initial design. While the UAT test is then measured by calculating the Likers' Summated Rating (LSR) scaling, respondents assess the system that has been built with a percentage score of 92.95% which means it is successful.